Welfare Reform and At‐Risk Mothers' Labour Supply1. Issue 2 (20th June 2013) - Ho, Christine
<x xml:space="preserve">Abstract</x> We analyse the impact of the early 1990s welfare waivers and the 1996 TANF reform in the United States on at‐risk mothers' labour supply behaviour using the PSID. We find that whereas the welfare waivers had limited impacts on at‐risk mothers, the TANF reform played an important role in encouraging those mothers to increase their labour supply at the intensive margin.